PENGARUH HARGA DIRI DAN KELOMPOK TEMAN SEBAYA TERHADAP PERILAKU KONSUMTIF PADA MAHASISWA GENERASI Z - Rahel Monica S. Simangunsong; Nenny Ika Putri; Karina Meriem Beru Brahmana (Psikologi Universitas Sari Mutiara Indonesia, 2021)
The purpose of this study was to determine the effect of self-esteem and peer groups on consumptive behavior among generation Z students in Medan City. This study uses quantitative research methods with the help of the SPSS for windows 17.00 program. This study uses three scales, namely the consumptive behavior scale which is arranged based on the consumptive behavior indicator according to Summartono (2002), the self-esteem scale which is based on the self-esteem aspect according to Coopersmith (1998), and the peer group scale which is arranged based on the characteristics of the peer group according to Santrock (2007). The subjects in this study were active students aged 18-25 years from 4 public and private universities in Medan, namely the University of North Sumatra (USU), Medan State University (UNIMED), University of HKBP Nommensen Medan (UHN), and the University of Muhammadyah North Sumatra (UMSU) Based on the hypothesis test, it is known that there is no effect of self-esteem and peer groups on consumptive behavior in generation Z students in Medan City with a significance value of 0.622.